The Effect of Service Quality, Price, and Promotion on Go-Mart Customer Loyalty with Satisfaction as Moderator at Bandar Lampung University - Trianisa Aldina Fitri Sudiana; Andala Rama Putra Barusman (Komunitas Dosen Indonesia, 2025)
This study examines the influence of service quality, pricing, and promotions on customer loyalty at Go-Mart, particularly among students from the Faculty of Economics and Business at the University of Bandar Lampung. Customer loyalty is defined as the commitment to continue using the services provided, which is essential for sustaining competitive advantage in today’s market. The research indicates that high service quality, reasonable pricing, and effective promotions significantly enhance customer satisfaction. This satisfaction, in turn, drives loyalty, thereby creating a positive feedback loop that benefits both the customer and the business. Employing a quantitative methodology, online questionnaires were distributed to 280 respondents, ensuring a diverse range of perspectives. Data analysis was conducted using Structural Equation Modeling (SEM), a robust statistical technique that allows for the assessment of complex relationships between variables. The findings reveal that all independent variables—service quality, pricing, and promotions positively influence customer loyalty, with customer satisfaction serving as a crucial mediator in these relationships. These results provide valuable insights for companies looking to develop more effective marketing strategies to boost customer loyalty in the digital age. By focusing on these key areas, businesses can enhance their offerings, ultimately leading to increased customer retention and loyalty.